A review on cerium oxide-based electrolytes for ITSOFC. Issue 5 (1st September 2012) - Babu, K. Suresh; Arunkumar, P.; Meena, M.
Abstract : Solid oxide fuel cells (SOFCs) generate electricity at very high efficiency with low to negligible emissions, making them as an attractive option for power generation. Though conventional SOFCs operate at 1000°C or more, current research is focused on reducing the operation to intermediate temperatures (300–600°C) without compromising the power density in order to develop economic and cost effective fuel cell systems for commercialization. Since electrolyte material significantly affects the operating temperature, one of the critical challenges is to design and develop electrolytes with an ionic conductivity of 0·1 S/cm. Reduction in operating temperature leads to an increase in electrolyte ohmic resistance losses as ionic transport is governed by thermal activation. Since 1960s fluorite structured cerium oxide-based electrolytes have been studied for engineering the ionic conductivity. Researchers have used various structural and technological modifications through doping, grain size reduction, development of multi-phase materials, and multi-layered thin films of cerium oxide-based electrolytes showing an improvement in ionic conductivity. The present work reviews the ionic conduction theory, development in designing cerium oxide-based electrolyte structure, and potential future directions towards low-temperature operations.